أثر التحول الرقمي على إنتاجية العاملين: دراسة قياسية بالتطبيق على القطاع العام بمصر - محمد، ياسمين عبدالرحيم سيد أحمد (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2023)
أصبح التحول الرقمي من التوجهات العالمية المعاصرة، والتي يجب السير نحوها من أجل مزيد من السرعة في انجاز المهام والمعاملات، ومن أجل توفير الوقت والجهد وخفض التكاليف، ومن أجل تحقيق كفاءة وفاعلية أكثر في كل المهام والأعمال المطلوب انجازها ومن أجل زيادة الإنتاجية. وهذا التحول الرقمي هو من دعامات تطبيق ونجاح أدارة الأعمال بشكل إلكتروني، لما يقدمه من نظم وإجراءات تكنولوجية تسهل ممارسة هذا النمط الإداري الحديث نسبيا من خلال تطويع المنظومة الإلكترونية لخدمة المهام الإدارية؛ فلقد أصبح العالم الافتراضي الرقمي متداخلاً في كل شيء، وينبغي الاستفادة من ذلك في سبيل تحقيق انطلاقة في الشركات والمؤسسات والقطاعات، ويعد التحول الرقمي إحدى الممارسات الحديثة نسبيا المطروحة على الساحة الإدارية، والتي تسعي كثير من الشركات والمؤسسات والمنظمات وأجهزة الحكومة المختلفة لتبنيها وتطبيقها. ومن أسباب دواعي التحول الرقمي علي سبيل المثال : هو الرغبة في تحسين أداء المنظمات، والتواصل السريع مع العملاء والمستهلكين والموردين، وتقديم نماذج جديدة من الخدمات الإلكترونية، وتوفير الوقت والجهد وخاصة في حالة بعد الأماكن، وتطبيق ثقافة الإدارة بلا أوراق وتحسين وزيادة إنتاجية العاملين، وفي ظل ما يواجهه العالم من الحين إلى الآخر من أزمات وجوائح تضطر كثير من المنظمات إلى الغلق بشكل جزئي، والتركيز على العمل عن بعد، والتواصل الرقمي والبحث الحالي يهدف إلى التعرف على أثر التحول الرقمي على رفع إنتاجية العاملين بالقطاع العام في مصر، ولتحقيق ذلك استخدمنا منهجية السلاسل الزمنية للدراسة القياسية، وتوصل البحث إلى وجود تأثير مهم لتكنولوجيا التحول الرقمي في زيادة إنتاجية العاملين والتي أوضحتها النتائج وأثبتت تغيراً وتحسن في مستوى إنتاجية العاملين بالقطاع محل البحث بفعل التحول الرقمي من خلال تأثير التكنولوجيا والاتصالات الحديثة، وأخيراً أوصى البحث إلى ضرورة وحتمية مواكبة الشركات والقطاعات إلى التطور التكنولوجي في عالم التحول الرقمي وتفعيلة في جميع القطاعات. Digital transformation has become one of the contemporary global trends, which must be followed in order to speed up the completion of tasks and transactions, in order to save time and effort and reduce costs, and in order to achieve more efficiency and effectiveness in all tasks and work to be accomplished and in order to increase productivity. This digital transformation is one of the pillars of the application and success of business management electronically, as it provides technological systems and procedures that facilitate the practice of this relatively modern management style. By adapting the electronic system to serve administrative tasks, the digital virtual world has become intertwined in everything, and this should be taken advantage of in order to achieve a breakthrough in companies, institutions and sectors. Digital transformation is one of the relatively recent practices introduced in the administrative arena, which many companies, institutions, organizations and various government agencies seek to adopt and apply. One of the reasons for digital transformation, for example: is the desire to improve the performance of organizations, Rapid communication with customers, consumers and suppliers, providing new models of electronic services, saving time and effort, especially in the case of remote places, applying the culture of paperless management, improving and increasing the productivity of workers, and in light of the crises and pandemics that the world faces from time to time, many organizations are forced to partially close, and focus on remote work, Digital communication and current research aims to identify the impact of digital transformation on raising the productivity of public sector workers in Egypt, and to achieve this we used the time series methodology of the standard study, and the research found that there is an important impact of digital transformation technology in increasing the productivity of workers, which was shown by the results and proved a change and improvement in the level of productivity of workers in the sector in question due to digital transformation through the impact of modern technology and communications, Finally, the research recommended the necessity and inevitability of keeping companies and sectors abreast of technological development in the world of digital transformation and activating it in all sectors.
Keywords: التحول الرقمي -- إنتاجية القوى العاملة -- أداء العاملين -- القطاع العام -- مصر